Book Review: Pragmatics of Social Media - Yuliani Kusuma Putri (Jurnal Sosioteknologi, 2022)
The book entitled "Pragmatics of Social Media" was edited by Christian Hoffmann and Wolfram Bublitz and published in 2017. This book is the 11th volume of the “Handbooks of Pragmatics” book series which consists of 13 separate volumes, the entire volume of the book provides an ample overview of the field of language studies, especially about Pragmatics. This book, published for the first time in Germany, was published by the publisher De Gruyter Mouton. This book has 724 pages consisting of 5 (five) subjects, namely (1) The nature of social media, (2) Social media platforms, (3) Social media and discourse, (4) Social media and identity, and (5) Social media functions.